Applying the guidelines: a quantitative content analysis of a state agency’s external communication - Ray, Jennifer (Kansas State University, 2015)
The purpose of this study was to identify how K-State Research and Extension (KSRE) has established and maintained its brand through external communication with target audiences. The three research objectives were to determine the extent to which, 1) branding guidelines were followed, 2) calls to action were provided, and 3) key audiences were targeted. A quantitative content analysis was conducted to assess a representative sample of all communication KSRE state employees published within one year, November 1, 2012 to October 31, 2013. The Social Exchange Theory (SET) served as the framework and research objectives were based on the concept of Integrated Marketing Communication (IMC). The study found the correct name of the organization appeared in only 56.6 % (n= 611) of units; appearances of images, graphics, and the official slogan were also minimal. Primarily, the study identified a need for increased specification and clarity in the guidelines in order to promote increased consistency. This study serves as a benchmark for future measurement, a basis for recommended changes, and a call for other state extension agencies to examine communication in similar studies. The researcher recommends the organization makes substantial edits and additions to the branding guidelines, provides employees with training, and implements a regular evaluation of communication efforts to monitor brand representation and communication effectiveness. Additionally, the researcher addresses the need for an IMC model specific to extension, to help communicators implement more strategic and measurable efforts.
Keywords: Extension communication; Land-grant communication; Integrated marketing communication; Brand management; External communication; Brand consistency; Agriculture, General (0473); Marketing (0338)